Public libraries in component cities social relevance of the San Pablo City Public Library - Ignacio, Gerald John D. (2014)
Public libraries are one of the oldest institutions that serve humanity. Through time, its function and definition has evolved in order to adapt to the ever changing needs of the society. From just being a primal repository of knowledge, it has become one of society's most important entities for the enhancement of the social fabric of a community.